Determinasi Kompetensi, Kompensasi, dan Komitmen pada Kinerja Perangkat Desa - Iradat I. Kuylo; Abdul Wahab Hasyim; Sulfi Abdulhaji; Muhammad Asril Arilaha (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study examines the impact of competence, compensation, and commitment on village officials' performance. Methodology/approach: Conducted in North Oba District, Tidore Islands City, this quantitative research surveyed 123 village officials using questionnaires. Data analysis utilized multiple linear regression with SPSS to assess relationships among variables. Results/findings: The findings reveal that competence (? = 0,368, p < 0,05) and compensation (? = 0,453, p < 0,05) have a significant positive effect on the performance of village officials. Competence, encompassing knowledge, skills, and attitudes, and compensation, including financial and non-financial rewards, were identified as critical performance drivers. However, commitment (? = 0,143, p > 0,05) did not demonstrate a statistically significant effect on performance, potentially due to the influence of external factors such as political dynamics in personnel management. Conclusions: Competence and compensation significantly influence the performance of village government apparatus, whereas commitment does not exhibit a significant effect. These findings highlight the critical importance of enhancing professional competencies and establishing a fair compensation system as key strategies to improve performance and the quality of public service delivery at the village level. Limitations: This study focuses on a single geographic area and excludes external factors such as organizational culture or policy frameworks that may affect performance. The exclusive use of quantitative methods limits insights into contextual and subjective dimensions. Contribution: This study contributes to public sector HRM theory and practice, especially in village governance, by offering policy-relevant insights on skill enhancement and fair compensation.